Feature Extraction Methods for Studying Surface Electromyography and Kinematic Measurements in Parkinson’s Disease - Rissanen, Saara M.; Kankaanpää, Markku; Tarvainen, Mika P.; Karjalainen, Pasi A. (IntechOpen, 2012)
None